The fate of the dead and the living at the Lord's Parousia: exegesis of 1 Thessalonians 1:9-10; 4:13-18; 5:1-11 - Owusu, Eric (New Testament studies in contextual exegesis, 2021)
"This book traces the roots of the Christian belief in resurrection and the afterlife as presented by Paul in First Thessalonians. The Ghanaian author adopted mainly the approach of History of Religion (Religionsgeschichte) to his study of the Pauline exhortations on the fate of the dead and the living at the Lord's parousia in First Thessalonians. He is of the view that neither the African Traditional Religion nor ancient Greek philosophy and mythology can give the background information on the Pauline exhortations in question but Paul's origin as a Jewish Pharisee who believed in the resurrection of the dead and valued this belief he inherited from Judaism. The book can help believers in Christ see death as an event which paves the way for them to begin a new life with God, their creator"--